What drives e-commerce repurchase intention? Mediating role of customer satisfaction - Salsabila Pavita Indraswari; Ahmad Mardalis; Sidiq Permono Nugroho (Journal of Enterprise and Development (JED), 2023)
Purpose — The main objective of this study is to evaluate the behavioral models of TAM (Technology Acceptance Model) and SDL (Service Dominant Logic). Its specific focus is to investigate how ease of use, servitization, and security impact repurchase intention in e-commerce. Additionally, this study aims to examine the mediating role of customer satisfaction.Method — This study utilized quantitative method which involved an online survey with 125 student participants. The sampling technique involved non-probability and purposive sampling. The validity and reliability of the outer model were assessed through SmartPLS analysis, while the smartPLS inner model was used to test hypotheses.Result — Our findings indicate that there is a direct impact of ease of use, servitization, and security on repurchase intentions in e-commerce. Additionally, we observed that perceived customer satisfaction serves as a mediator in the behavioral model of e-commerce repurchase intention.Contribution — This study provides empirical evidence on how ease of use, servitization, and security impact customer repurchase intentions in e-commerce, with customer satisfaction serving as the mediator and TAM and SDL behavioral models as the primary frameworks for analysis.